2005
DOI: 10.1128/jvi.79.11.7087-7094.2005
|View full text |Cite
|
Sign up to set email alerts
|

Enterovirus 70 Binds to Different Glycoconjugates Containing α2,3-Linked Sialic Acid on Different Cell Lines

Abstract: Sialic acids are a ubiquitous family of negatively charged sugar molecules found on the surfaces of mammalian cells, usually at the termini of glycans attached to glycoproteins, glycosphingolipids, and the proteoglycan keratan sulfate (2, 10, 72). Sialic acid is an essential component of cell surface receptors for a variety of microorganisms and microbial toxins (2,34,47). Members of at least eight different virus families-Ortho-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
53
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(55 citation statements)
references
References 76 publications
(89 reference statements)
1
53
0
1
Order By: Relevance
“…The other serotypes of HEV-D (EV68 and EV70) use DAF as a receptor in HeLa cells (Karnauchow et al, 1996;Blomqvist et al, 2002). EV70 also uses sialic acid-containing receptors in a variety of other human cell lines (Alexander & Dimock, 2002;Haddad et al, 2004;Nokhbeh et al, 2005). Our results suggest that EV94 does not need DAF to infect RD cells.…”
Section: Discussionsupporting
confidence: 52%
“…The other serotypes of HEV-D (EV68 and EV70) use DAF as a receptor in HeLa cells (Karnauchow et al, 1996;Blomqvist et al, 2002). EV70 also uses sialic acid-containing receptors in a variety of other human cell lines (Alexander & Dimock, 2002;Haddad et al, 2004;Nokhbeh et al, 2005). Our results suggest that EV94 does not need DAF to infect RD cells.…”
Section: Discussionsupporting
confidence: 52%
“…In many studies, glycosylation has been shown to affect the viral attachment or penetration steps via the modification of cellular receptors or viral envelope glycoproteins. For instance, the O-linked glycoproteins of ␣2,3-or ␣2,6-linked sialic acids were shown to play important roles during infection by IAV and other viruses, including the coxsackievirus A24 variant and enterovirus 70 (42)(43)(44)(45). Furthermore, the envelope proteins of many viruses, such as human immunodeficiency virus type 1, HCV, Ebola virus, and herpes simplex virus 1, have been shown to be modified by O-linked glycosylation, which influences the attachment of viral virions to the cell surface (42,(46)(47)(48).…”
Section: Discussionmentioning
confidence: 99%
“…The cellular receptors for several members of the Picornaviridae family have been described, including decay-accelerating factor (DAF), intercellular adhesion molecule 1 (ICAM-1), low-density lipoprotein receptor (LDL-R), sialic acid, coxsackie and adenovirus receptor (CAR), various integrins, and heparan sulfate (25,26,34,44,49,50,53,57,61,62,75). CVA24v and EV70 replicate in both conjunctival and corneal cells in vivo and in vitro (50,76).…”
mentioning
confidence: 99%